Authors’ rights and their scope - Pradhan, Pustun (Bodhi: An Interdisciplinary Journal, 2013)
Allocation of exclusive rights enabling the authors and other producers of intellectual property to exclude non-paying users is the core aspect of copyright law. This exclusion was a foremost precondition before the market for goods containing intellectual property could come into existence. Exclusive rights are essentially monopoly rights but the extent of this monopoly is largely determined, among other factors, by the nature and scope of these rights. While these rights are critical to secure incentives to the creators so that adequate creation and development of intellectual property may take place, they may also impede the free flow of information and hence retard the creation. These rights are therefore drawn with proper delimitations to ensure that information and ideas are not unduly monopolized to the detriment of social and economic development. This paper looks into the nature and scope of the rights granted to the authors. It has six sections. Bodhi: An Interdisciplinary Journal, 5, 2011, Page 111-131 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8047